Correlates of health-related quality of life in Thai patients with alcohol dependence - Pichai Saengcharnchai (2018)
© 2016, Copyright © Taylor & Francis Group, LLC. This study aimed to examine the correlates of health related quality of life in Thai patients with alcohol dependence. The amount of alcohol intake was calculated by timeline followback chart and the health related quality of life was determined by Short Form–36 Health Survey. The means of the Short Form–36 Physical Component and Mental Component Summary were 67.43 (18.74) and 64.45 (20.90), respectively. Stepwise linear regression models showed the number of heavy drinking days was significantly correlated with the Physical Component Summary and Mental Component Summary. Such moderate correlations suggest that drinking and health related quality of life measures might tap different aspects of alcohol outcomes and should be concurrently administered.